Trisomy 8 Associated Clonal Cytopenia Featured With Acquired Auto-Inflammation and Its Response to JAK Inhibitors - Fu, Yakai; Wu, Wanlong; Chen, Zhiwei; Gu, Liyang; Wang, Xiaodong; Ye, Shuang (Frontiers in Medicine, 2022)
Abstract Objects: It has been recognized the nexus between trisomy 8 and auto-inflammatory features in myelodysplasia syndrome. Recent research about VEXAS syndrome proved clonal hematopoiesis could interfere with innate immune system far before occurrence of hematological malignancies. We reported a case series of clonal cytopenia with auto-inflammatory features in trisomy 8 patients. Methods: A total of six patients with isolated trisomy 8 excluded from MDS was retrospectively collected from the Department of Rheumatology, Renji Hospital, Shanghai. The clinical presentations and treatment outcomes were presented. Results: We report patients with trisomy 8 shared the auto-inflammatory features of recurrent fever, arthralgia, gastrointestinal involvement, and elevated inflammatory markers, especially hyperferritinemia, in addition to hematological findings such as macrocytic anemia and cytopenia of other lineages but without myelodysplasia. The symptoms of this disorder responded to the treatment of glucocorticoids but difficult to taper. JAK inhibitors were introduced to four patients with enhanced response along with glucocorticoids sparing effect and good tolerance. Conclusion: Clonal cytopenia harboring trisomy 8 presenting with auto-inflammatory features was identified. JAK inhibitor may be a promising anti-inflammatory option.